Improvement Priorities: Public Hospital Service Quality - Dachyar M.; Farizal; Ti Alicia (MATEC Web of Conferences, 2018)
Patients’ satisfaction in public hospitals in Jakarta is decreased due to the increase participant of outpatients using national health insurance. One of the principle influenced satisfaction is services. The purpose of this research is to get priority improvement of service quality dimension. ServQual method is used to obtain the patient’s perception and expectation gap on hospital services. Analytical Hierarchy Process (AHP) is used to obtain the dimension importance weight. Five experts were involved on choosing the appropriate service dimension. Questionnaires were given to 400 patients. Results showed that the largest gap on overall services dimension and sub-dimension are cleanliness, comfort of check room and bathroom. The weight of importance is included, results show the priority improvement of trust dimension and sub-dimension doctor is checking the patient’s condition correctly.